Role of Estrogen Receptor, Progesterone Receptor, Human Epidermal Growth Factor Receptor Type 2/neu, and Ki-67 in Surface Epithelial Ovarian Tumors and Its Histopathological Correlation - Deshpande, Sapna Shreyas; Halgale, Mohasin Jakirhusain; Chimankar, Pradnya Manikrao; Vadavadgi, Akshay V; Pawar, Vishrabdha Rahul (Annals of Pathology and Laboratory Medicine, 2025)
Background: This study aims to evaluate the expression of estrogen receptor (ER), progesterone receptor (PR), HER-2/neu, and Ki-67 in epithelial ovarian tumors and their correlation with various clinicopathologic variables. Methods: This study included 50 cases of surface epithelial ovarian tumors. Formalin-fixed paraffin-embedded blocks were prepared from the surgical resection specimens. Hematoxylin and Eosin (H & E) stained sections were examined. Appropriate blocks with tumor tissue were selected for immunohistochemical (IHC) analysis. IHC was performed using commercially available monoclonal antibodies for ER, PR, Ki-67, and HER-2/neu. Results: Amongst a total of 50 malignant ovarian tumors encountered, the most common tumor was of the serous type (30 cases, 60%). Expression of ER was mainly noted in the serous and endometrioid type of surface epithelial tumors. Expression of PR was less in comparison to ER. Expression of HER-2/neu was rarely found. Out of the total 50 cases studied, 10 were post-chemotherapy patients. Expression of Ki-67 in post-chemotherapy patients was reduced. Conclusion: ER positivity is seen in most of the serous tumors. Ki-67 nuclear expression should be considered as a prognostic factor. HER-2/neu overexpression is sparse in our study, so further research with a large sample size, followed by gene amplification, is necessary to rule out HER-2/neu expression in surface epithelial ovarian tumors.